Les déplacements entre Bruxelles et sa périphérie : des situations contrastées - Mathieu Strale (Brussels Studies)
Mobility between Brussels and its outskirts is a multidimensional issue involving socioeconomic, environmental and political challenges. However, precise data on this issue are relatively limited. In this context, this article proposes to address the issue through an empirical geographical analysis. Thus, the differentiated conditions and ways of travelling to Brussels from its metropolitan area emerge, and are summarised within a typology.